Variation in Soil Microbial Communities Along an Elevational Gradient in Alpine Meadows of the Qilian Mountains, China - Duan, Yulong; Lian, Jie; Wang, Lilong; Wang, Xuyang; Luo, Yongqing; Wang, Wanfu; Wu, Fasi; Zhao, Jianhua; Ding, Yun; Ma, Jun; Li, Yulin; Li, Yuqiang (Frontiers in Microbiology, 2021)
Bacterial, archaeal, and eukaryota diversity in mountainous areas varies along elevational gradients, but details remain unclear. Here, we use a next-generation sequencing method based 16S/18S rRNA to reveal the soil microbial diversity and community compositions of alpine meadow ecosystems along an elevation span of nearly 2,000 m (1936-3896 m) in China’s Qilian Mountains. Both bacterial and eukaryota diversity increased linearly with increasing elevation, whereas archaeal diversity increased, but not significantly. The diversity patterns of several phyla in the bacterial, archaeal, and eukaryota communities were consistent with the overall elevational trend, but some phyla did not follow this pattern. The soil microbial community compositions were shaped by the coupled effects of regional climate and local soil properties. Intra-domain links were more important than inter-domain links in the microbial network of the alpine meadows, and these links were mostly positive. The bacteria formed more connections than either archaea or eukaryota, but archaea may be more important than bacteria in building the soil microbial co-occurrence network in this region. Our results provide new visions on the formation and maintenance of soil microbial diversity along an elevational gradient, and have implications for microbial responses to climate change in alpine ecosystems.